RESEARCH ON MARKETING OF PRODUCTS AT KODAIKANAL TOURISM CENTRE – DINDIGUL DISTRICT - Diana; Poornimarani (International Journal of Research -GRANTHAALAYAH, 2016)
The study intends to find answers to the problems and shortcomings in tourism infrastructure development in the study area and tourism support services such as quantity and quality of public transport, accommodation, food, bank, park facility, shopping, medical facilities and so on. The opinion of and suggestions from the tourist respondents incorporated herein would provide guidelines for future course of action to be followed in Kodaikanal.